Building a Site-Based Interactive Content Management System Using PHPNuke - Pande Putu Agus Ang; Soenarto Usna,Drs. MMSI (Jurnal Sistem Informasi, 2004)
The writing is clear on how to build an interactive website where site visitors can participate in the activities and development of the site's content. This site is a comprehensive site where all the lawyer-categories of sites can be carried out for various things in accordance with the desired criteria. Therefore, the authors propose an alternative to building an interactive site-based Content Management System using PHPNuke.